2008
DOI: 10.1017/s0007485308006081
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mechanisms to mitochondrial electron transport inhibitors in a field-collected strain ofTetranychus urticaeKoch (Acari: Tetranychidae)

Abstract: A Belgian field strain (MR-VP) of Tetranychus urticae (Koch) (Acari: Tetranychidae) exhibits different levels of resistance to four frequently used METI (mitochondrial electron transport inhibitor)-acaricides, i.e. tebufenpyrad, fenpyroximate, pyridaben and fenazaquin. Resistance factors for these compounds were 184, 1547, 5971 and 35, respectively. A 23.5-fold increase in 7-ethoxy-4-trifluoromethylcoumarin O-deethylation activity suggested that metabolic resistance through elevated levels of cytochrome P450 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 45 publications
8
133
0
3
Order By: Relevance
“…The strain was controlled by regular foliar applications of commercial formulations of the following acaricides: tebufenpyrad, pyridaben, clofentezine, hexythiazox, bifenthrin, fenbutatin oxide, abamectine, and oxamyl. Resistance to mitochondrial electron transport inhibitor (METI) acaricides is well characterized in MR-VP (104). The Marathonas (MAR-AB) strain was isolated from a heavily sprayed rose greenhouse near Athens (Greece) in 2009.…”
Section: Methodsmentioning
confidence: 99%
“…The strain was controlled by regular foliar applications of commercial formulations of the following acaricides: tebufenpyrad, pyridaben, clofentezine, hexythiazox, bifenthrin, fenbutatin oxide, abamectine, and oxamyl. Resistance to mitochondrial electron transport inhibitor (METI) acaricides is well characterized in MR-VP (104). The Marathonas (MAR-AB) strain was isolated from a heavily sprayed rose greenhouse near Athens (Greece) in 2009.…”
Section: Methodsmentioning
confidence: 99%
“…This acaricide, launched in 1998, is usually classified among mite growth inhibitors, together with clofentezine and hexythiazox, older acaricides that cause similar symptoms (Marčić, 2003;Krämer & Schirmer, 2007), but whose exact mode of action is unknown. On the other hand, Nauen & Smagghe (2006) Marčić, 2007;Marčić et al, 2007;Van Pottelberge et al, 2009;Marčić et al, 2010). These two acaricides are the only new compounds used for control of eriophyoid mites as well .…”
Section: Acaricides Acting On Growth and Development Targetsmentioning
confidence: 99%
“…The insensivity of acetylcholinesterase is the most common type of organophosphorous resistance in T. urticae (Cranham & Helle, 1985;, Tsagkarakou et al, 2002Khajehali et al, 2010;Kwon et al, 2010a). Metabolic resistance mediated by carboxylesterases was found in majority of cases of resistance development to pyrethroids in this species (Ay & Gűrkan, 2005;van Leeuwen et al, 2005b, while the oxidative metabolism appears to play a major role in resistance to METI-acaricides Kim et al, 2004Kim et al, , 2006van Pottelberge et al, 2009). The results of numerous conventional genetic studies indicate that in most cases single major gene controls inheritance of resistance in spider mites (Cranham & Helle, 1985;.…”
mentioning
confidence: 99%
“…It has been estimated that the spider mite, T. urticae has evolved resistance to more than 80 acaricides to date (Knowles, 1997;Devine et al, 2001;Choi et al, 2004;Van Pottelberge et al, 2008 and) and resistance has been reported from many countries. As for mechanisms of resistance to acaricides with new modes of action (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As for mechanisms of resistance to acaricides with new modes of action (e.g. Abamectin, fenpyroximate, chlorphenapyr, METI-acaricides, spirodiclofen) enhanced detoxification in T. urticae strains has been reported (Devine et al, 2001;Nauen 2001and 2002;Kim et al, 2004a and b;Van Leeuwen et al, 2006;Van Pottelberge et al, 2008 and). …”
Section: Introductionmentioning
confidence: 99%